2011
DOI: 10.1093/rheumatology/ker013
|View full text |Cite
|
Sign up to set email alerts
|

Services for people with ankylosing spondylitis in the UK—a survey of rheumatologists and patients

Abstract: This is the first study to explore the services available to people with AS in the UK. Almost one-third of patients are not seen in rheumatology departments and therefore may be under-treated. For those who are seen, access to anti-TNF drugs and other therapies remains an issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 16 publications
3
31
0
Order By: Relevance
“…The authors found that only 14.6% of patients had ever attended a disease education session; furthermore, only 12.4% of patients had been invited to attend a patient education program. Of those patients who had attended an education session, 99.1% found them ''very useful'' or ''quite useful'', as defined by a questionnaire [50]. This result supports the concept that patient education is deemed important by the patients themselves, and that more needs to be done to ensure that patients are offered appropriate education.…”
Section: Increasing Knowledge and Awareness For Patients And Physicianssupporting
confidence: 63%
See 1 more Smart Citation
“…The authors found that only 14.6% of patients had ever attended a disease education session; furthermore, only 12.4% of patients had been invited to attend a patient education program. Of those patients who had attended an education session, 99.1% found them ''very useful'' or ''quite useful'', as defined by a questionnaire [50]. This result supports the concept that patient education is deemed important by the patients themselves, and that more needs to be done to ensure that patients are offered appropriate education.…”
Section: Increasing Knowledge and Awareness For Patients And Physicianssupporting
confidence: 63%
“…As part of a project launched by the National Ankylosing Spondylitis Society (NASS) aiming to develop recommendations for improving care for AS patients in the UK, healthcare service utilization was examined [50]. The authors found that only 14.6% of patients had ever attended a disease education session; furthermore, only 12.4% of patients had been invited to attend a patient education program.…”
Section: Increasing Knowledge and Awareness For Patients And Physiciansmentioning
confidence: 99%
“…Delay in diagnosis of SpA has been described in women 5,9,10 and in both sexes 6,7,[11][12][13][14][15][16]20,26,27,29,30,32,33,35,38,39,40,44,45,46 , and although Bandinelli 23 observed less diagnostic delay in women than in men, in most of the papers where delay was compared between men and women, it was greater in women 8,17,18,19,21,22,28,31,34,37,41,42,43,47,48 . This implies that patients have had medically unsolved disorders for a long time, have continued searching for a diagnosis and treatment, or are being erroneously diagnosed and managed 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows the main characteristics of the 42 studies on diagnostic delay in SpA included in this systematic review 1,2,3,[8][9][10][11][12][13][14][15][16][17][18]19,20,21,22,23,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]48 . The review included 23,883 patients (67.6% men, 32.3% women).…”
Section: Methodsmentioning
confidence: 99%
“…The progressive ankylosis of affected joints is currently irreversible and it is, therefore, logical that early diagnosis and treatment offers the best opportunity to improve its prognosis. Several studies have shown a delay of more than 8 years between the onset of symptoms and diagnosis, with consequent delay in starting an effective therapy (Feldtkeller et al, 2003;Hamilton et al, 2011). This is a critical period clinically, with diagnosis frequently occurring after significant irreversible radiological damage has already occurred.…”
Section: Introductionmentioning
confidence: 99%